Pengaruh Model Pembeajaran Kooperatif Tipe Student Team Achievement Division Terhadap Hasil Belajar Siswa Tema 3 Subtema 2 Keberagaman Mahkluk Hidup di Lingkungan Ku Kelas IV SD Negeri 122357 Pematang Siantar - Sri Mariana Panjaitan; Yanti Arasi Sidabutar; Natalina Purba (Jurnal Pendidikan Dasar Islam, 2023)
This research aims to see the influence of the Student Team Achievement Division Type Cooperative Learning Model on Student Learning Outcomes Theme 3 Subtheme 2 Diversity of Living Creatures in My Environment Class IV of State Elementary School 122357 Pematang Siantar. This research used a type of Pre-Experimental Design research. The sample in this research was all 23 class IV students at SD Negeri 122357 Pematang Siantar. The sampling technique in this research uses nonprobability sampling with a saturated sample type. Saturated sampling is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small. Hypothesis testing is used to determine whether student learning outcomes using the STAD type cooperative learning model are more influential than students taught using conventional learning. So the t_count > t_table value uses a significance level of 0.05 and df=24, namely 17.294 > 1.711. This means that the learning model has an influence on learning outcomes in lesson material Theme 3 Subtheme 2 Diversity of Living Creatures in My Environment Class IV at SD Negeri 122357 Pematangsiantar. If the learning model is done well, it will greatly influence the quality of student learning in the classroom.